Rapid detection of Pseudomonas aeruginosa by glycerol one-pot RAA/CRISPR-Cas12a method - Wei, Lijian; Luo, Shihua; Zhou, Weijie; Ren, Baoyan; Li, Miao; Liang, Lina; Li, Xuebin; Wei, Guijiang (Frontiers in Chemistry, 2025)
Pseudomonas aeruginosa (PA), an opportunistic pathogen commonly responsible for hospital-acquired infections, poses significant threats to human health. To enable rapid and reliable PA detection while effectively mitigating aerosol contamination risks inherent in conventional methods. We developed a glycerol one-pot Recombinase-aided Amplification (RAA)/CRISPR-Cas12a method. Four result reading methods were established: Fluorescence Detection (FD), Blue Light Irradiation Detection (BLD), and Ultraviolet Irradiation Detection (UID), as well as Lateral Flow Chromatography Strip (LFS). The glycerol one-pot RAA-CRISPR/Cas12a method demonstrated high specificity and sensitivity in detecting the PA-specific lasB gene. The detection limit reached 1.20 × 10-4 ng/μL (fluorescence-based) and 1.20 × 10−3 ng/μL (LFS-based). In validation against 64 clinical isolates, compared to conventional PCR, the assay achieved 100% sensitivity, specificity, and accuracy in lasB detection. In conclusion, the glycerol one-pot RAA/CRISPR-Cas12a method provides a rapid, sensitive, and straightforward platform, providing a promising approach for clinical diagnosis of PA and environmental surveillance applications.